Respon Peserta Didik Terhadap Physics Education Technology (PhET) Simulation Pada Materi Rangkaian Listrik Kelas VI SD Bina Persada - Mohamad Yudiyanto; Annisa Mayasari; Farhana, Hana Rizki; Deni Soidin (Prodi PGMI STAI Sabili Bandung, 2022)
This research aims to explain the use of information and communication technology as one of the web-based learning media in an application, namely PhET Simulation learning media. As we know in science learning in elementary schools, there are many learning materials that are still difficult for teachers to explain because the material presented is abstract (virtual / imaginary) so that students do not understand the concept of learning. With the existence of PhET simulation media, in the learning process, both teachers and students will collaborate in exploring various things about the world of natural knowledge so that students are more enthusiastic during teaching and learning activities. PhET simulations are designed to make learning more innovative (web-based), fun and of course collaborative between teachers and students. PhET simulations help students understand learning concepts, especially in science learning in elementary school, where many natural science materials are still abstract and require semi-concrete or concrete media to inform learners, one alternative is the use of learning media for PhET simulations. The result of the research show that PhET simulation is an effective learning media to increase the effectiveness of student learning, and can help student learn without having to use a real laboratory, by utilizing PhET simulation media it can also improve students’ ICT literacy skills, beside that using PhET simulation is very easy and can be understoodnin occording with science subject matter, PhET simulation can also be used for independent study at home without having to be suoervised by teacher at school.